Cannabis Use in Pregnant and Breastfeeding Women: Behavioral and Neurobiological Consequences - Navarrete, Francisco; García-Gutiérrez, María Salud; Gasparyan, Ani; Austrich-Olivares, Amaya; Femenía, Teresa; Manzanares, Jorge (Frontiers in Psychiatry, 2020)
Nowadays, cannabis is the most consumed illicit drug. The global prevalence of the use of cannabis in 2017 was estimated in 188 million of people, 3.8% of worldwide population. Importantly, the legalization of cannabis in different countries, together with the increase in the apparent safety perception may result in a great variety of health problems. Indeed, an important concern is the increase of cannabis use among pregnant and breastfeeding women, especially since the content of delta9-tetrahidrocannabinol (THC) is currently around 2-fold higher than it was 15-20 years ago. The purpose of this study was to review cannabis use during pregnancy and breastfeeding including: epidemiological aspects, therapeutic or preventive strategies and experimental considerations and results from animal models of perinatal cannabis exposure to analyze the underlying neurobiological mechanisms and to identify new therapeutic approaches. A recent report revealed that among pregnant women aged 15 to 44, last month cannabis use prevalence was over 4.9%, raising to 8.5% in the 18 to 25 years old age range. Pre-natal and post-natal exposure to cannabis may be associated with critical alterations in the newborn infants that are prolonged throughout childhood and adolescence. Briefly, several reports revealed that perinatal cannabis exposure was associated with low birth weight, reduction in the head circumference, cognitive deficits (attention, learning and memory), disturbances in emotional response leading to aggressiveness, high impulsivity or affective disorders, and higher risk to develop a substance use disorder. Furthermore, important neurobiological alterations in different neuromodulatory and neurotransmission systems have been associated with cannabis consumption during pregnancy and lactation. In spite of the evidences pointing out the negative behavioral and neurobiological consequences of cannabis use in pregnant and breastfeeding women, there are still limitations to identify biomarkers that could help to establish preventive or therapeutic approaches. It is difficult to define the direct association specifically with cannabis avoiding other confusing factors, co-occurrence of other drugs consumption (mainly nicotine and alcohol), lifestyle or socioeconomic factors. Therefore, it is necessary to progress in the characterization of short- and long-term cannabis exposure-related disturbances.